2011
DOI: 10.5090/kjtcs.2011.44.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Video-Assisted Thoracic Surgery (VATS) Lobectomy for Pathologic Stage I Non-Small Cell Lung Cancer: A Comparative Study with Thoracotomy Lobectomy

Abstract: BackgroundSurgical treatment of stage I non-small cell lung cancer (NSCLC) can be performed either by thoracotomy or by employing video-assisted thoracic surgery (VATS). The aim of this study was to evaluate the feasibility of VATS lobectomy for pathologic stage I NSCLC.Material and MethodsBetween December 2003 and December 2007, 529 patients with pathologic stage I NSCLC underwent lobectomies (373 thoracotomy, 156 VATS). Patients in both groups were selected after being matched by age, gender and pathologic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…Consistent with our study, Yan et al [6] showed that VATS lobectomy decreased the acute postoperative pain, reduced inflammatory cytokine release, exhibited less impairment in pulmonary function, shorter chest tube duration and consequently shorter hospitalization days, in NSCLC patients. Interestingly, Park et al [17] presented evidence that the surgical outcomes in VATS lobectomy were comparable in success to TOS in NSCLC patients diagnosed early for the disease and VATS is a feasible operation associated with shorter hospitalization, which is generally preferred by patients. Jiang et al [7] also compared the two surgeries, within the context of adjuvant chemotherapy, and showed that VATS had fewer delays or dose reductions and better compliance than TOS.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with our study, Yan et al [6] showed that VATS lobectomy decreased the acute postoperative pain, reduced inflammatory cytokine release, exhibited less impairment in pulmonary function, shorter chest tube duration and consequently shorter hospitalization days, in NSCLC patients. Interestingly, Park et al [17] presented evidence that the surgical outcomes in VATS lobectomy were comparable in success to TOS in NSCLC patients diagnosed early for the disease and VATS is a feasible operation associated with shorter hospitalization, which is generally preferred by patients. Jiang et al [7] also compared the two surgeries, within the context of adjuvant chemotherapy, and showed that VATS had fewer delays or dose reductions and better compliance than TOS.…”
Section: Discussionmentioning
confidence: 96%
“…The multi-institutionaland the national studies by Philips et al and Paul et al, respectively, did not include cancer stage [14,15]. Furthermore, many studies have been limited to Stage 1 lung cancer [16,17,19,21]. Cancer stage could be a predictor for intraoperative complications; a higher stage is often associated with a larger and more centrally placed tumour, making the risk of damaging the large vessels greater when dissecting the lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Two years after the publication by Yan et al Korean researchers published a 1:1 propensity-matched study that considered 270 patients with stage I NSCLC (10). No statistical differences in postoperative complications were found between the 2 groups, but the VATS group had a significantly shorter hospital stay (p<0.05).…”
Section: Video-assisted Thoracoscopic Surgery Lobectomy and Lymph Nodmentioning
confidence: 99%